Implementasi Teknik Equivalence Partitions untuk Pengujian Black Box pada Sistem Informasi DAPODIKDASMEN - Putra, Alvin Pratama; Nurdin, Noviar; Rondonuwu, Rio Valentino; Kusyadi, Irpan (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
DAPODIKDASMEN (Data Pokok Pendidikan Dasar dan Menengah) is an application that is very important for schools to be used in managing all data related to institutional, curriculum, student data, teacher data, and employee data, as well as data on facilities and infrastructure of all schools in Indonesia and schools- Indonesian schools abroad. This application is quite complex, if something goes wrong can result in large losses. For this reason, testing of features in the DAPODIKDASMEN application is needed to ensure that there are no problems that cause losses, especially for stakeholders (stakeholders), this test is carried out to provide assurance that the DAPODIKDASMEN application is error free and suitable for use. Testing the DAPODIKDASMEN application is proposed by Black Box using the Equivalence Partitions technique so that errors / defects can be identified and can be corrected immediately. The results of testing with the Equivalence Partitions technique can find errors that exist due to errors in the pre-coding stage, as well as unintentional errors in coding, so that the resulting application can be guaranteed to be of high quality and in accordance with established requirements.